Change in inflammation in out-patient COPD patients from stable phase to a subsequent exacerbation - Erik Bathoorn; Jeroen JW Liesker; Dirkje S Postma; Gerard H Koëter; Marco van der Toorn; et al (International Journal of COPD, 2009)
Erik Bathoorn1, Jeroen JW Liesker1, Dirkje S Postma1, Gerard H Koëter1, Marco van der Toorn2, Sicco van der Heide2, H Alec Ross3, Antoon JM van Oosterhout2, Huib AM Kerstjens11Department of Pulmonology; 2Laboratory of Allergology and Pulmonary Diseases, Groningen Research Institute for Asthma and COPD (GRIAC), University Medical Center Groningen, University of Groningen, the Netherlands; 3Department of Chemical Endocrinology, Radboud University Nijmegen Medical Centre, the NetherlandsBackground: Inflammation increases during exacerbations of COPD, but only a few studies systematically assessed these changes. Better identification of these changes will increase our knowledge and potentially guide therapy, for instance by helping with quicker distinction of bacterially induced exacerbations from other causes.Aim: To identify which inflammatory parameters increase during COPD exacerbations compared to stable disease, and to compare bacterial and non-bacterial exacerbations.Methods: In 45 COPD patients (37 male/8 female, 21 current smokers, mean age 65, FEV1 52% predicted, pack years 38) sputum was collected during a stable phase and subsequently during an exacerbation.Results: Sputum total cell counts (9.0 versus 7.9 × 106/mL), eosinophils (0.3 versus 0.2 × 106/mL), neutrophils (6.1 versus 5.8 × 106/mL), and lymphocytes (0.07 versus 0.02 × 106/mL) increased significantly during an exacerbation compared to stable disease. A bacterial infection was demonstrated by culture in 8 sputum samples obtained during an exacerbation. These exacerbations had significantly increased sputum total cell and neutrophil counts, leukotriene-B4, myeloperoxidase, interleukin-8 and interleukin-6, and tumor necrosis factor-α (TNF-α) levels, and were also associated with more systemic inflammation compared to exacerbations without a bacterial infection. Sputum TNF-α level during an exacerbation had the best test characteristics to predict a bacterial infection.Conclusion: Sputum eosinophil, neutrophil, and lymphocyte counts increase during COPD exacerbations. The increase in systemic inflammation during exacerbations seems to be limited to exacerbations caused by bacterial infections of the lower airways. Sputum TNF-α is a candidate marker for predicting airway bacterial infection.Keywords: chronic obstructive pulmonary disease, exacerbation, inflammation, sputum induction